How Medical Students Manage Depression, Anxiety, and Stress: A Cross-Sectional Study - Jonathan Shaw; Ashley Lai; Sasha Singh; Seung Rim Yoo; Maha Fathali; Laura Stuck; James Hagerty; Van Le; Jisu Shin; Charles Lai; Peter Bota; Aaron Jacobs (JMIR Formative Research)
AbstractGiven the established challenging nature of medical school, first- and second-year medical students were surveyed on their feelings of stress alongside their coping mechanisms; the study found a higher level of stress among second-year medical students, indicating a need for support during difficult transition periods.